A Grammar of Yeyi. A Bantu Language of Southern Africa. - Lusekelo, Amani (AAeO - Afrikanistik-Aegyptologie-Online, 2009)
The structuring of this volume is quite impressive as the author manages to organize the massive materials into chapters that facilitate collectively the understanding of facts about the Bantu language Yeyi. The author uses a huge amount of illustrative examples, totaling 1.341, which are supported by subsequent good descriptions.